Synthesis and Cytotoxic Evaluation of Novel Platinum(II) Complexes with C2‐Asymmetric and C2‐Symmetric Chiral Vicinal Diamines. Issue 1 (8th January 2013) - Zhang, Chen; Liu, Hongrui; Yang, Qing; Chang, Jun; Sun, Xun
Abstract A series of new platinum(II) complexes with C2‐asymmetric and C2‐symmetric 1, 2‐diamines were designed and synthesized by convenient methods, involving samarium diiodide induced reductive coupling as the key step. The results of cytotoxicity showed that compounds (R, R)‐11a and (S, S)‐11a, two novel platinum(II) complexes with asymmetric 1, 2‐diamines, exhibited more potent cytotoxicity than that of oxaliplatin against all leukemia cell lines. Interestingly, (R, R)‐11a and (S, S)‐11a demonstrated less potent activity against three solid cancer cell lines than that of oxaliplatin, which indicated that these two compounds may only selectively inhibit the leukemia cell lines. In contrast, (R, R)‐15a and (S, S)‐15a, two platinum(II) complexes with symmetric 1, 2‐diamines, showed similar cytotoxicity to that of oxaliplatin against all leukemia cell lines and more potent activity against solid cancer cell lines. Further flow cytometry data indicated that (R, R)‐11a could obviously arrest leukemia K562 cells in G2/M phases.